Failure analysis of railroad concrete crossties in the center negative flexural mode using finite element method. (May 2017) - Yu, Hailing; Marquis, Brian P; Jeong, David Y
Finite element models are developed for the railroad concrete crossties and are employed to analyze their center negative flexural responses to two center binding conditions: a center negative moment test condition and a hypothetical deteriorated ballast support condition. These conditions can lead to center negative flexural cracks and, eventually, sudden, catastrophic failure of the concrete ties when the loads reach critical magnitudes. When the concrete ties fail completely and consecutively in track, the gage can be sufficiently widened to cause derailment. The finite element results are first validated with the available test data, and the validated finite element models are then employed to obtain and evaluate the cracking/failure patterns and force–displacement characteristics of the concrete ties in the center negative flexural mode in static and dynamic analyses. The finite element analyses predict the critical wheel loads above which catastrophic tie failure is likely to occur, and the dynamic critical failure loads are shown to depend on the center binding ballast support conditions as well as the worn concrete tie conditions. The worn tie conditions that include bottom abrasion and prestress loss can significantly reduce the dynamic critical failure loads and, thereby, adversely affect the center negative flexural performance of the concrete ties.